Association between smoking and serum uric acid in Korean population: Data from the seventh Korea national health and nutrition examination survey 2016. Issue 7 (February 2019) - Kim, Seong-Kyu; Choe, Jung-Yoon
Abstract : Abstract: The aim of this study was to identify any association between serum uric acid and smoking status using data from the Seventh Korea National Health and Nutrition Examination Survey (KNHANES VII-1) 2016 of the Korean population. This study used a cross-sectional design and analyzed 5609 subjects aged ≥ 19 years among 8150 participants enrolled in the KNHANES VII-1 2016. Smoking status was classified into current smokers, never smokers, and ex-smokers. Hyperuricemia was defined as > 7.0 mg/dL for men and > 6.0 mg/dL of serum uric acid for women. Association between smoking and serum uric acid/hyperuricemia was assessed by Pearson's or Spearman's correlation analyses and multivariate logistic regression analysis showing odds ratio (OR) and 95% confidence interval (CI). A significant difference in serum uric acid according to smoking status was identified in female ( P < .001) but not in male subjects ( P = .069). In female subjects, current smokers and ex-smokers showed higher serum uric acid than never smokers ( P < 0.001 of both). Serum uric acid was associated with smoking status in female but not male subjects ( r = 0.057, P = .001 and r = 0.025, P = .220, respectively). There was significant difference of smoking status between female subjects with and without hyperuricemia ( P < .001). Current smokers had 2.7 times higher likely to have hyperuricemia in female, compared to never smokers (OR 2.674, 95% CI 1.578 – 4.531, P < .001). This study revealed that smoking was closely associated with serum uric acid in female but not in male subjects in Korean population.